Qualificação dos espaços livres da UFT: proposta para o entorno do CUICA - Martins, Claudia Moraes (Universidade Federal do Tocantins, 2021)
The lack of spaces for leisure and rest within the Federal University of Tocantins (UFT), Palmas campus, together with the importance of having quality free spaces, generated the need for qualification of these spaces at the university. During the construction of the campus there was no concern with the areas surrounding the buildings, generating free spaces without planning and consequently an idle space, without use, disregarding all the existing potential. The objective of the work in question is to propose a landscape intervention focusing on open spaces as a qualifying element of the campus, seeking to improve the life of the academic population, through the treatment of spaces through the qualification of free spaces, supporting the collective coexistence, appropriation of the spaces, improves the environmental and life quality of the campus users, promoting spaces for leisure and physical and mental rest, in addition to proportioning a characteristic identity for the place.